(untitled) (Revista Dialectus - Revista de Filosofia, 2023)
In the lecture Nietzsche: l’homme devant la mort de dieu, Gabriel Marcel highlights the extraordinary topicality of Nietzsche’s thought and figure. The French philosopher seems to say to his hearers: Nietzsche is here, among us, he does not belong to the past, but, on the contrary, he is the most contemporary of contemporaries. Nietzsche’s philosophy of the death of God is a mine of ideas and insights that need to be enhanced. There is still much about him to be discovered. Nietzsche, then – and nihilism as such – is by no means outdated, precisely because, Marcel exclaims, before claiming to have left him behind, it is better to make sure we have reached him.